2014
DOI: 10.1111/adj.12158
|View full text |Cite
|
Sign up to set email alerts
|

General and craniofacial development are complex adaptive processes influenced by diversity

Abstract: Complex systems are present in such diverse areas as social systems, economies, ecosystems and biology and, therefore, are highly relevant to dental research, education and practice. A Complex Adaptive System in biological development is a dynamic process in which, from interacting components at a lower level, higher level phenomena and structures emerge. Diversity makes substantial contributions to the performance of complex adaptive systems. It enhances the robustness of the process, allowing multiple respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
47
2
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(54 citation statements)
references
References 40 publications
3
47
2
2
Order By: Relevance
“…It forms part of the complex adaptive system (CAS) of oro-facial development whereby epithelial tissues and neural crest mesenchyme are involved in delicate signalling pathways with multiple molecular events that overlap each other [1][2][3][4]. For a system to be considered as complex and adaptive, it should exhibit the principles of self-organisation and self-adaptation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It forms part of the complex adaptive system (CAS) of oro-facial development whereby epithelial tissues and neural crest mesenchyme are involved in delicate signalling pathways with multiple molecular events that overlap each other [1][2][3][4]. For a system to be considered as complex and adaptive, it should exhibit the principles of self-organisation and self-adaptation.…”
Section: Introductionmentioning
confidence: 99%
“…Separate genetic pathways and genetic/epigenetic/environmental interactions occur simultaneously throughout the dental developmental process; this is evidence of multitasking. The intricate and multilevel processes that occur during odontogenesis demonstrate the characteristics of a CAS [1,[5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…The human body is a complex adaptive system, and human development is a complex adaptive process [10]. This research has shown that both teeth and fingerprints are interconnected, yet they still have a degree of autonomy.…”
Section: Methodsmentioning
confidence: 93%
“…Human development is a complex adaptive process that is influenced by genetic, epigenetic and environmental factors [10]. Genes interact with epigenetic and environmental elements and create complex networks within cells, and from this process the higher level tissues are formed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation